Respuesta :

The simplified expression of [tex]x^{-2/3} . x^{6/7}[/tex] is [tex]x^{4/21}[/tex]

How to simplify an expression?

The expression [tex]x^{-2/3} . x^{6/7}[/tex] can be simplified as follows:

using law of indices,

xⁿ . xᵇ = xⁿ⁺ᵇ

Therefore,

[tex]x^{-2/3} . x^{6/7}[/tex] = [tex]x^{-2/3 + 6/7}[/tex]

[tex]x^{-2/3 + 6/7} = x^{ -14+18/ 21}[/tex]

[tex]x^{-2/3 + 6/7} = x^{ -14+18/ 21} = x^{4/21}[/tex]

learn more on expression here: https://brainly.com/question/403991

#SPJ1

ACCESS MORE